Limited genetic polymorphism of the Plasmodium vivax low molecular weight rhoptry protein complex in the Colombian population (2010)
Proteins involved in parasite adhesion and invasion are considered the best candidates for the development of asexual blood-stage antimalarial vaccines. Such vaccine candidates should be accessible by the immune system and have limited diversity. Considering the promising results obtained in previous trials by immunizing monkeys with the rhoptry-associated proteins 1 and 2 (RAP-1 and RAP-2), here we assessed the genetic variability of the Plasmodium vivax rap-1 and rap-2 genes isolated from Colombian parasite populations. Limited sequence diversity was found in these genes, possibly as a result of a functional/structural restriction. The presence of several haplotypes at relatively low frequencies and the excess of singleton mutations suggests that a demographic process might be affecting the loci. Our results support the inclusion of PvRAP-1 and PvRAP-2 in the design of an antimalarial subunit-based vaccine against P. vivax, which would avoid inducing allele-specific immunity. © 2009 Elsevier B.V. All rights reserved.